Resubmit my Information Security Thesis? - You must be joking! - Armstrong, Helen; Ynstrom, L. (Springer, 2007)
This paper presents a model for use by students and supervisors embarking upon higher degrees by research with specific application to information security. The model details a set of questions to be asked in preparing for the research in order to ensure a well planned and cohesive research project and written thesis.